2023
DOI: 10.1111/age.13303
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study for eumelanin pigmentation in chicken plumage using a computer vision approach

Abstract: Chicken plumage colouration is an important trait related to productivity in poultry industry. Therefore, the genetic basis for pigmentation in chicken plumage is an area of great interest. However, the colour trait is generally regarded as a qualitative trait and representing colour variations is difficult. In this study, we developed a method to quantify and classify colour using an F2 population crossed from two pure lines: White Leghorn and the Korean indigenous breed Yeonsan Ogye. Using red, green, and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It has been reported that mutations in the MTAP gene are associated with nevus count and melanoma development (Kvaskoff et al, 2011). Genomic variants identified in the MTAP are associated with plumage and dermal pigmentation in the F2 population crossed from White Leghorn and the Yeonsan Ogye (Cha et al, 2023; Heo et al, 2023). Functional gene expression analysis of Silkie and White Leghorn chicken embryos during early embryonic stages indicated distinct patterns of MTAP expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mutations in the MTAP gene are associated with nevus count and melanoma development (Kvaskoff et al, 2011). Genomic variants identified in the MTAP are associated with plumage and dermal pigmentation in the F2 population crossed from White Leghorn and the Yeonsan Ogye (Cha et al, 2023; Heo et al, 2023). Functional gene expression analysis of Silkie and White Leghorn chicken embryos during early embryonic stages indicated distinct patterns of MTAP expression.…”
Section: Discussionmentioning
confidence: 99%
“…A genomic feature related to the role of the genes present in the sexual chromosomes needs to be better investigated. Indeed, it has been demonstrated that the Z chromosome in chicken contains the loci directly or indirectly implicated in shank and eggshell color ( Heo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%